2006
DOI: 10.1175/mwr3235.1
|View full text |Cite
|
Sign up to set email alerts
|

Transition of the Rainfall Characteristics Related to the Moistening of the Land Surface over the Central Tibetan Plateau during the Summer of 1998

Abstract: This paper describes a transition of rainfall characteristics related to the moistening of the land surface over the central Tibetan Plateau. This transition was observed three weeks after the onset of the summer rainy season of 1998. The objective is to clarify the potential of the plateau surface to modify the characteristics of monsoon rainfall. Summer rain events were first separated according to large-scale conditions into three types: one with a near-surface heat low and a Tibetan upper high, one with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…As part of GAME-IOP, coordinated intensive observations were made over the TP, under the cooperation between GAME-Tibet, and the second Chinese Tibetan Plateau scientific experiment (TIPEX). Some of the meteorological results during the GAME-IOP over the TP were already reported elsewhere (e.g., Uyeda and Yamada 2001;Xu et al 2002;Wang et al 2003;Fujinami et al 2005;Yamada and Uyeda 2006).…”
Section: Introductionmentioning
confidence: 64%
“…As part of GAME-IOP, coordinated intensive observations were made over the TP, under the cooperation between GAME-Tibet, and the second Chinese Tibetan Plateau scientific experiment (TIPEX). Some of the meteorological results during the GAME-IOP over the TP were already reported elsewhere (e.g., Uyeda and Yamada 2001;Xu et al 2002;Wang et al 2003;Fujinami et al 2005;Yamada and Uyeda 2006).…”
Section: Introductionmentioning
confidence: 64%
“…They forced the model using latent and sensible heat fluxes over the paddy field observed in GAMEHuaihe Basin Experiment (HUBEX), and found that meso-scale cloud systems embedded in the Meiyu (Baiu) front developed through moisture supply to ABL and change of moist static stability of the lower troposphere. The change of land-atmosphere interaction and its impact on cloud/precipitation systems through the seasonal change of soil moisture (surface wetness) condition was also observed over the Tibetan Plateau during the GAME-Tibet (Yamada and Uyeda 2006). Yamada (2007) simulated the feature over the plateau, showing that dry elevated surface on the Tibetan Plateau is favorable for more convective rain whereas wetter surface condition is favorable for stratiform cloud but with more rainfall amount as shown in Fig.…”
Section: Role Of Vegetationmentioning
confidence: 75%
“…Yamada and Uyeda (2006) focused on the differences in synoptic conditions, such as the prevailing cumulus convection with a dominant Tibetan High (Upper High; UH type) and the passage of a synoptic disturbance (TROUGH; TR type), and they detected that a cumulus structure of the UH type changes with the moistening of the land-surface. Mid-latitude oscillation effects on this intraseasonal variability of precipitation activity over the TP.…”
Section: Introductionmentioning
confidence: 99%